Binge Drinking, Cannabis Co-Consumption and Academic Achievement in First Year University Students in Spain: Academic Adjustment as a Mediator - Páramo, María Fernanda (Int J Environ Res Public Health, 2020)
Little is known about how binge drinking or the combination of binge drinking and cannabis consumption affect academic achievement in students during the transition to university, or about the mechanisms that mediate this relationship. The purpose of this study was to evaluate the association between this pattern of alcohol/cannabis consumption and academic achievement, considering academic adjustment as a possible mediator. A total of 258 Spanish, first-year university students (145 females and 113 males), enrolled in undergraduate degree courses, were categorized into three groups on the basis of their patterns of alcohol/cannabis consumption: control, binge drinkers and co-consumers. The findings showed a significant effect of the combined binge drinking/cannabis consumption, but not of binge drinking alone, upon academic achievement and academic adjustment. Grade point average (GPA) and academic adjustment were lower in the co-consumers than in the other groups. Regarding the mediation effect, 34.33% of the impact of combined alcohol/cannabis use on GPA was mediated by academic adjustment. The combined consumption of alcohol and cannabis led to difficulties in adaptation to academic life, which in turn contributed to poorer performance at university. The implications of the findings are discussed.